KNOWLEDGE AND IMPLEMENTATION OF OUTCOME-BASED EDUCATION IN THE MATHEMATICS DEPARTMENT OF MAPUA UNIVERSITY - Carlos, John Christoper G.; Dacoco, John Paolo Eriche G. (International Journal of Research -GRANTHAALAYAH, 2021)
An increasing global demand for competitive graduates set off different universities around the world to shift their educational approach to Outcome-Based Education (OBE). Assessment on the status of the implementation of Outcome-Based Education is beneficial to various sectors of the educational body by using the results as their benchmark in maximizing the effectiveness of the system to their learners. The purpose of the study is to assess the level of implementation of OBE and its association with the scholastic characteristics of the students. The study is a descriptive research that involved the faculty and students of the mathematics department of Mapua university. The results showed that the respondents have a very high level of knowledge and high level of practice on the implementation of OBE. Results also showed that the level of implementation of OBE is associated with the scholastic characteristics of the students. It is then recommended that teachers would continue implementing OBE in mathematics courses as it has great impact on the behavior and performance of the students. In this context the department should come up with a monitoring program so that the effective implementation of OBE is ensured.